2016
DOI: 10.3351/ppp.0010.0003.0005
|View full text |Cite
|
Sign up to set email alerts
|

Family Policy: an integrated approach?

Abstract: Following the result of the EU Referendum and the emergence of a new Prime Minister the direction of family policy in England remains to be clarified. The future of flagship initiatives of the previous administration such as the Troubled Families Programme and the Life Chances Strategy remain uncertain. Taking advantage of the hiatus to take stock, this article raises concerns regarding the effects of previous ad hoc family policy development with particular reference to parenting support and relationship supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A second option to improve outcomes of children in home‐visiting services is to involve them more directly in services intended for the whole family. Although whole‐family approaches show promising results (Bolt & Van der Zijden, 2021; Majoribanks & Davies, 2016; Thoburn et al, 2013), professionals often experience considerable difficulties in involving all family members in these services. Several studies have suggested care professionals experience considerable challenges in building multiple alliances with family members (Busschers & Boendermaker, 2015; Tausendfreund et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A second option to improve outcomes of children in home‐visiting services is to involve them more directly in services intended for the whole family. Although whole‐family approaches show promising results (Bolt & Van der Zijden, 2021; Majoribanks & Davies, 2016; Thoburn et al, 2013), professionals often experience considerable difficulties in involving all family members in these services. Several studies have suggested care professionals experience considerable challenges in building multiple alliances with family members (Busschers & Boendermaker, 2015; Tausendfreund et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Parenting has been repeatedly conceptualised as one of the core mechanisms through which cycles of deprivation-key to understanding health and other inequalities-are perpetuated (Gillies, 2007). From Conservative minister Keith Joseph's seminal speech on cycles of deprivation in the early 1970s (Denham, 2002;Welshman, 2005Welshman, , 2014, through to Labour Prime Minister Tony Blair's Respect Action Plan in the 1990s (Respect Task Force, 2006;Welshman, 2014) and on to the Troubled Families programme as introduced by the Coalition Government (Cameron, 2011;Marjoribanks & Davies, 2016), the focus has been on breaking undesirable historic cycles which have at their centre "poor parenting". Implicit in these policies is the idea that problem families beget problem families.…”
Section: Introductionmentioning
confidence: 99%